2014
DOI: 10.1016/j.ecoleng.2014.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced polychlorinated biphenyl removal in a switchgrass rhizosphere by bioaugmentation with Burkholderia xenovorans LB400

Abstract: Phytoremediation makes use of plants and associated microorganisms to clean up soils and sediments contaminated with inorganic and organic pollutants. In this study, switchgrass (Panicum virgatum) was used to test for its efficiency in improving the removal of three specific polychlorinated biphenyl (PCB) congeners (PCB 52, 77 and 153) in soil microcosms. The congeners were chosen for their ubiquity, toxicity, and recalcitrance. After 24 weeks of incubation, loss of 39.9 ± 0.41% of total PCB molar mass was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 73 publications
3
30
0
Order By: Relevance
“…This species was tested for PCB degradation in the rhizosphere of Panicum virgatum L. and was found to be responsible for the removal of 47.3 % of the PCB pollutants present (Liang et al 2014). Recently, Burkholderia sp.…”
Section: Bioremediationmentioning
confidence: 99%
“…This species was tested for PCB degradation in the rhizosphere of Panicum virgatum L. and was found to be responsible for the removal of 47.3 % of the PCB pollutants present (Liang et al 2014). Recently, Burkholderia sp.…”
Section: Bioremediationmentioning
confidence: 99%
“…Another approach that bypasses plant genetic engineering hur dles and possible issues with the use of genetically modified plants involves phytore mediation combined with soil bioaugmentation using natural bacterial isolates that degrade the contaminants of interest. Such a study demonstrated that B. xenovorans LB400 could enhance phytoremediation of polychlorinated biphenyls by switch grass [88].…”
Section: Phytoremediation: the Expression Of Bacterial Dioxygenases Imentioning
confidence: 95%
“…The soil microcosm set-up procedure has been described previously (Liang et al 2014b; Meggo and Schnoor 2013). Briefly, a mixture of PCB 52, PCB 77 and PCB 153 (99% pure) (Accustandard Inc., New Haven, CT) was dissolved in hexane and then applied to the PCB free-soil (Nodaway series, silt loam from Middle Amana, Iowa, USA) at a target concentration of 500 ng g −1 each (wet weight).…”
Section: Methodsmentioning
confidence: 99%